Medical Informatics in China: Healthcare IT Trends, Academic and Research Developments - Luo, S.; Zhang, K.; Li, B. (Yearbook of Medical Informatics, 2010)
Objective: Describing the challenges and advances in medical informatics in China from the perspectives of hospital information systems, workforce, and academic, and research advances.Methods: The paper summarizes information from the CMIA (China Medical Informatics Association and findings reported by CHIMA (China Hospital Information Management Association), including a White Paper on China Hospital Information Systems.Results: Biomedical and Health Informatics has grown considerably during the past decade in China, and is an important component of proposed government planning that includes development of healthcare cards, clinical workflow path rules, and rural medicine. CMIA has strengthened as an organization promoting education, research and academic activities, while CHIMA has sponsored many hospital-based activities, including workshops on technical and workforce IT priorities related to proposed reforms of China’s healthcare system.Conclusions: China’s challenges and opportunities in biomedical informatics and healthcare IT are considerable, with the former requiring greater promotion of academic research and educational opportunities through CMIA to support the burgeoning development of healthcare IT systems throughout the country. National and international collaboration and exchanges could lead to very useful comparative studies, Recommendations by CHIMA to the national government and academia focus on organizational and workforce standards, roles, and defining career paths for HIT professionals as well as CME education in healthcare informatics at the graduate university.
Keywords: Biomedical informatics education and research; healthcare Iiformation technology; market analysis; professional development